2020
DOI: 10.1017/dmp.2019.152
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Operation During a Disaster – Hospital Multi-Component Emergency Center (HMCEC)

Abstract: A hospital’s operating modes can be divided into three main levels of operation: routine, mass-casualty, and interim states that require procedures and resources beyond the routine capacity. Regardless of the nature of the event and the needs, the medical staff has to be prepared for a sudden increase in demand for service that could overwhelm the functional capacity and safety standards of the hospital. In any sort of an emergency event, the hospital has to fulfill two goals: First is to be able to sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…By including a series of indicators (Proximity, Event, Multitude, Overcrowding, Temporary Ward Reduction Capacity, and Time Shift Slot) widely identified in the literature as crucial to determine the effectiveness of the re-organization procedure following an MCI, 3,[17][18][19] the PEMAAF score also allows to avoid unjustified activations of the hospital MCI plan, thus safeguarding elective and routinary hospital activities, thus not hampering the continuity of care and assistance. 11 The PEMAAF score enabled the MCI management within the Metropolitan City of Milan to reach a much higher plateau of innovativeness, by enhancing communication and response strategies between the DC and the regional trauma network, through the establishment of a common language and shared operating procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By including a series of indicators (Proximity, Event, Multitude, Overcrowding, Temporary Ward Reduction Capacity, and Time Shift Slot) widely identified in the literature as crucial to determine the effectiveness of the re-organization procedure following an MCI, 3,[17][18][19] the PEMAAF score also allows to avoid unjustified activations of the hospital MCI plan, thus safeguarding elective and routinary hospital activities, thus not hampering the continuity of care and assistance. 11 The PEMAAF score enabled the MCI management within the Metropolitan City of Milan to reach a much higher plateau of innovativeness, by enhancing communication and response strategies between the DC and the regional trauma network, through the establishment of a common language and shared operating procedure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A hospital MCI plan features different levels of activation, from a "standby level" to upper levels that require withholding routine activities to effectively manage the large influx of patients by re-organizing staff, stuff, and structure. 3 Since activating a hospital MCI plan might result in the cancellation of elective diagnostic and therapeutic procedures, as well as elective surgery and ambulatory activities, thus impacting the provision of basic health services for the population, medical responders and hospital managers should carefully weigh the decision of activating the plan. 4 In the current literature, many after action reports (AARs) of hospital responses documented the increasing need to avoid an excessive mobilization of hospital resources compared to the actual needs, preserving routine hospital activities, and avoiding unjustified expenses.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] While carrying out their current tasks, hospitals in crisis situations must be able to respond to a high volume of patients and injured who have been imposed upon them as a result of disasters. [ 15 ] The results of a study revealed the preparedness of Iranian hospitals at a moderate level (40%–60%) and a low level (13%). [ 16 ] Frequent assessment and monitoring to identify weaknesses and challenges and proper planning can contribute to improving hospital preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…The medical system—including prehospital emergency services, hospitals and primary healthcare providers—must increase its capacity on short notice and switch into a response mode, which requires a well-functioning command structure that is capable of adapting patient flows, medical care and other attendant adjustments. At the same time, the system must be prepared to manage a situation in which the hospitals themselves may be threatened or damaged by the incident [ 4 ]. Managing a complex and dynamic situation, such as a major incident, requires adjusting organizational and medical procedures at both individual and organizational levels [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decision-making is key to an effective crisis response [ 4 ]. In crises, decision-making is time-sensitive and based on uncertain information and vague situational awareness [ 8 ].…”
Section: Introductionmentioning
confidence: 99%